Application of the Webtoon Media to Increase Student’s Reading Comprehension - Rosmiana, Sri; Jabri, Umiyati; Musdalifah, Musdalifah; Iqra, Iqra (Sublim: Jurnal Pendidikan, 2023)
This research was found out whether the application of the webtoon media increases students' reading comprehension. A quasi experimental design was used in this research with the experimental class and the control class. The populations were students of SMK PGRI Enrekang for the academic year 2021/2022. The samples of this study were students of class X OTKP (15 students) as the experimental group and students of class X AKL (15 students) as the control group. This sample was taken by cluster sampling technique. This research applied the webtoon application media to the experimental group and the folktales to the control group. The instrument of this research was reading test. It used to determine students' reading comprehension in learning English. The researcher found that the use of webtoon media could improve the student’s reading comprehension of class X OTKP of SMK PGRI Enrekang because the average score after being given post-test treatment which was 85.00 higher than the control was post-test grade is 75.00. This proves that the experimental group is in to the good category. Based on the data, the researcher concludes that the webtoon media can improve students' reading comprehension.